STUDENTS’ PERCEPTIONS TOWARDS USING GOOGLE SLIDES AND GOOGLE CLASSROOM AS ONLINE COLLABORATIVE TOOLS IN MANDARIN LEARNING - Chong Oi Leng; Chan Yann Sheng; Dr. Chun Keat Yeap; Choo Peng Tan (Journal of Islamic, Social, Economics and Development, 2021)
Covid-19 outbreak in Malaysia had a major impact on education. Lecturers have toshift from conventional face-to-face teaching to Open and Distance Learning (ODL) tocontinue delivering knowledge to their students. It was a big challenge for lecturers in theteaching of Mandarin as a foreign language which include listening, speaking, reading andwriting skills. This situation would inevitably affect the learning outcome of the subject.Therefore, lecturers are exposed to technological learning tools and applied flipped classroomapproach in teaching which prior use Google Applications namely Google Slides (a web-basedpresentation program, allowing comment and edit in real-time among teammates and lecturer)and Google Classroom (a web service which enables lecturer to create, share, comment andevaluate assignments in a collaborative teaching and learning environment) in Mandarincourse. The use of technology in teaching is not only to enhance students’ learning but also toequip students with the technological and collaborative tools while preparing them for futureacademic. Surveys were conducted to a government university’s undergraduates takingIntroductory Mandarin Level 1 in government undergraduate to elicit student perceptions ofusing the said applications to do language learning task and the effectiveness in building acollaborative learning environment. The results showed that this approach managed to boostup students’ participation in online learning, majority of the students prefer using suchapplications for future courses given that they can benefit from the lecturer’s immediate writtenfeedback and easy access of course materials.